ARTIKEL REVIEW, PEMANFAATAN TEPUNG IKAN UNTUK PENINGKATAN GIZI PANGAN - Achmad Syauqibik; Junianto Junianto (Universitas Mataram, 2024)
Fishmeal is a processed fish product that has the potential to improve food nutrition. This article aims to review the utilization of fishmeal in improving the nutrition of food products. The method used was a literature study and systematic review by analyzing 26 research articles published between 2014-2024 and 1 ministry report in 2020. Data were analyzed descriptively comparatively, focusing on the preparation of fishmeal, proximate composition of fishmeal, and proximate composition of food products resulting from fishmeal substitution. Results showed that the best method of making fishmeal was steaming and fat extraction, resulting in a brighter and cleaner flour. The proximate composition of fishmeal varies depending on the type of fish. Substitution of fishmeal in food products such as cookies, flakes, pizza bases, and pastries significantly increased the nutrient content, especially protein, calcium, and phosphorus, while decreasing the moisture content. Despite this, the nutritional content of these products still meets quality standards and is safe for consumption. Fishmeal is effective in increasing the nutritional value of food products, making it a promising alternative for food diversification and fortification to address malnutrition in the community.